Seasonal Income Determinants of Vegetable Crops Grown by Farmers in Baharaich District of Up - K. Srinivasa Rao, B. Padma Narayan (International Journal of Modern Agriculture, 2020)
The present paper want to analyse the factors responsible for determination of seasonal like Kharif, Rabi, and Zaid and total income levels of sample farmers in Bahraich, where the low level of vegetable crops area under cultivation in this state. More specifically, in this paper we want to examine the various inputs like expenditure on seeds, irrigation, fertilisers, pesticides, labour and transport cost influencing the determinants of Kharif, Rabi and Zaid seasons and total income of sample farmers in Bahraich. To achieve the objectives of this paper primary data has collected through multiple random sampling in this district. The results indicate that during Kharif season farmers income highly influenced by two factors significantly, whereas during Rabi season farmers income influenced by only one factor and during zaid season farmers income influenced by three factors and total income influenced by two factors significantly.